Recht sprechen über "besondere Gebilde" – die koloniale Gerichtsbarkeit und das Reichsgericht; Court Rulings with Regard to "Special Territorial Entities" – Colonial Jurisdiction and the German Reichsgericht - Jakob Zollmann (Rechtsgeschichte - Legal History, 2023)
– Recent historiography has shown how European rule and trade in the colonies shaped the law and the jurisprudence of courts in both the colonies and the metropole. Based on the case law of the highest German courts, in particular the Supreme Court (Reichsgericht), this article traces court practice in Germany and in the German »protectorates« (Schutzgebiete) as it related to colonial trade and rule. First, the article highlights a number of colonial legal issues that were tried in German courts before the German Empire formally became a colonial power in 1884. It then analyses the structure of the so-called »non-native jurisdiction« in the German colonies as an element of colonial state order. A hierarchy of courts was established that reached up to the Reichsgericht in Leipzig. Finally, the article analyses concrete decisions of the senates of the Reichsgericht in criminal matters that were based on colonial facts and / or colonial legal questions. These court decisions indicate how the colonies were exoticised in German jurisprudence or, on the contrary, if necessary normalised in order to correspond to (colonial) political objectives in the Kaiserreich.
Keywords: 340; German imperial Supreme Court (Reichsgericht); administration of justice; colonial laws; Africa; imperialism